Strategi Pengembangan Wisata Taman Hiburan Pantai Kenjeran Kota Surabaya - Sajidah, Ummu; M, Meirinawati (Socius: Jurnal Penelitian Ilmu-Ilmu Sosial, 2025)
Tourism development has an important role in driving national development and increasing local revenue. Such development requires proper strategic management to plan and implement policies effectively. The Surabaya City Government through the Surabaya City Culture, Youth, and Sports, and Tourism Office is developing tourism, one of which is the Kenjeran Beach Amusement Park destination which is experiencing instability in the number of tourist visits. This study aims to describe the tourism development strategy of Kenjeran Beach Amusement Park, Surabaya City. This research uses descriptive qualitative methods with data collection methods using observation, interviews, documentation, and literature studies. The focus of this research is based on the theory (Amerta, 2019) consisting of Attraction, Accessibility, Amenity, Ancillary (Tourism Organization). The results showed that the development of Kenjeran Beach Amusement Park, including: (1) Attraction is realized in the addition of artificial attractions and cultural attractions; (2) Access includes road infrastructure, traffic signs, directions, adequate parking, digital ticketing services, and public transportation access; (3) Amenity includes facilities that are quite complete and in accordance with tourism characteristics, but need to be optimized; (4) Ancillary is realized in the implementation of daily monitoring and evaluation as well as cross-sector cooperation with OPD in Surabaya City, local communities, to the private sector. However, more intensive human resource development and promotion are still needed.